Impact of long-term cryopreservation on serum proteome and metallome: Implications for Biobank quality control - Meng Lu; Xiongshun Liang; Wanna Xu; Hongxing Tan; Junan Yan; Xuqiao Hu; Wenxu Hong (PLoS ONE, 2026)
Biobanks constitute a cornerstone of modern biomedical research, yet the effects of long-term storage on biospecimen integrity are not fully characterized. This study systematically evaluated the impact of prolonged cryopreservation on the metallomic and proteomic profiles of human serum. We analyzed 400 serum samples from the Shenzhen Chronic Disease Risk Factor Surveillance Project, including 200 long-term and 200 short-term cryopreserved specimens from healthy adults. Inductively coupled plasma mass spectrometry (ICP-MS) was used to quantify ten metals: vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), copper (Cu), zinc (Zn), selenium (Se), rubidium (Rb), strontium (Sr), and cesium (Cs). Proteomic profiling was performed via liquid chromatography-tandem mass spectrometry (LC-MS/MS). The analysis quantified 682 proteins, with 242 showing significant abundance changes (fold change > 1.5, P < 0.05; 176 up-regulated, 66 down-regulated). Functional enrichment revealed these changes were linked to immune response, metabolic pathways, and antioxidant activity (P < 0.05). Concentrations of V, Mn, Fe, Zn, Rb, and Cs were significantly altered in long-term versus short-term stored samples ( P < 0.05). Moreover, long-term cryopreservation substantially reshaped the inter-element correlation networks. In summary, prolonged storage significantly modifies the serum metallome and proteome, potentially affecting the validity of research conclusions derived from biobanked materials. Consequently, storage duration must be rigorously considered and adjusted for in the design and interpretation of future large-scale retrospective studies utilizing archived specimens.